Pythium insidiosum sp. nov., the etiologic agent of pythiosis. - De Cock, A W (1987)
Pythium insidiosum sp. nov., the etiologic agent of pythiosis, a cosmopolitan disease of horses, cattle, and dogs, is described and illustrated.